Antibiotic treatment of signs and symptoms of pulmonary exacerbations: A comparison by care site. Issue 5 (19th December 2014) - Schechter, Michael S.; Regelmann, Warren E.; Sawicki, Gregory S.; Rasouliyan, Lawrence; VanDevanter, Donald R.; Rosenfeld, Margaret; Pasta, David; Morgan, Wayne; Konstan, Michael W.
Summary Background Antibiotic treatment of cystic fibrosis pulmonary exacerbations is inconsistent. Previous research has indicated that intravenous antibiotics are used more frequently at sites with better pulmonary function but it is not clear under what circumstances they are prescribed. Method Pediatric care sites enrolled in the Epidemiologic Study of Cystic Fibrosis were ranked by median FEV1 % predicted of children they followed. Reported presence of new signs and symptoms of a pulmonary exacerbation (PEx) and antibiotic treatment within 21 days were compared between those in the highest vs. those in the other quartiles, and adjusted for sociodemographic and clinical characteristics of patients. Result Highest quartile sites had a total of 2, 454 children eligible for this analysis; lower quartile sites had a total of 5, 487. The odds of having a PEx at highest vs. lower sites varied with how the PEx was defined, but high quartile sites were uniformly more likely to treat PEx with antibiotics. The adjusted odds ratio for treatment with any antibiotics of a PEx defined by the occurrence of one or two new signs and symptoms was 1.24 (95% CI 1.10, 1.40); for treatment of a PEx defined by the occurrence of three or four new signs and symptoms was 1.50 (95% CI 1.06, 2.11); and for treatment of a PEx defined by a drop of FEV1 by ≥–15% was 1.33 (1.10, 1.60). The adjusted OR for treatment of these PEx with IV antibiotics was 1.11 (0.94, 1.32), 1.90 (1.32, 2.72), and 1.33 (1.10, 1.60), respectively. Conclusion ESCF care sites in the highest quartile for FEV1 were more likely to prescribe antibiotics when patients present with either mild or overt evidence of PEx. While this may not be the only reason that their patients have superior median FEV1, it is likely an important contributor. Pediatr Pulmonol. 2015; 50:431–440. © 2014 Wiley Periodicals, Inc.